Instructional Practices Facilitating Cross-National Interactions in the Undergraduate Classroom - Yefanova, Diana N.; Montgomery, Mary Lynn; Woodruff, Gayle A.; Johnstone, Christopher J.; Kappler, Barbara (Journal of International Students, 2018)
We examine pedagogical practices that facilitate international and domestic students’ interactions on two campuses of a U.S. public university. Findings highlight the central role of the instructor in supporting student interactions via pair and group work and collaborative assignments that result in increased understanding of class content. The study highlights the need to intentionally address learning outcomes of cross-national interactions, such as communicative and intercultural skills, as students did not always view the benefits of such interactions in the same way as their instructors did.